Sosialisasi Pencegahan Stunting sebagai Upaya Peningkatan Kualitas Kesehatan Bayi dan Anak di Kecamatan Munjul, Kabupaten Pandeglang - Anis Fuad; Ika Arinia Indriyany (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Sultan Ageng Tirtayasa, 2023)
As one of the national priority programs included in the National Action Plan to Reduce Stunting Rates, stunting still needs to be solved. Various policies and programs implemented by the government will only run optimally and effectively in reducing the prevalence of stunting if partnerships with universities accompany them in creating interventions. This intervention is needed to change the community's mindset regarding providing adequate and balanced nutrition at 1000 days of life to prevent stunting. In Pandeglang in 2022, the prevalence of stunting is still at 28.4%, still above the average figure for Banten Province, which is 20.0%. Previously in 2021, the prevalence of stunting in Pandeglang Regency reached 39.5%. This figure is far from the Indonesian Government's target to reduce stunting by only 14% in 2024. Therefore this community service is here to help raise awareness in the community regarding the dangers of stunting. Three activities were carried out: Socialization of a Clean, Healthy Lifestyle; Stunting Socialization; and Family Planning Village Socialization. With this activity, the community will become aware of preventing stunting from an early age, starting from the smallest scope, namely the family.